Reducing TSS and COD of Leachate with Constructed Wetland using Water Jasmine (Echinodorus palaefolious) and Spider Plant (Chlorophytum comosum) - Mohamad Mirwan; Thineza Ardea Pramesti (Future Science, 2023)
Leachate is water that comes from piles of rubbish that seeps in with dissolved or suspended material from the decomposition of rubbish. The contents of leachate include BOD, COD, pH, ammonia-nitrogen, heavy metals and suspended solids. One type of leachate treatment is a constructed wetland. A constructed wetland is a treatment that is engineered with a planned and controlled wastewater treatment system that involves the function of plants, media, and microorganism. This constructed wetland in this research uses subsurface flow with a continuous method on a laboratory scale. In this research, there were several variations such as plants, sampling times and discharge. The plants used are water jasmine (Echinodorus palaefolius) and spider plant (Chlorophytum comosum). With variations in discharge of 5L/day, 7L/day, 9L/day as well as variations in sampling time on the 6th, 8th, 10th, 12th, 14th day. The best TSS and COD reduction results in this study were at discharge of 5L/day on sampling time on the 14th day of 96,3% and 94,4% for water jasmine and 92,6% and 88,9% for spider plants. The pH and temperature in this study were observed for 14 days and it was found that the lowest pH and temperature for water jasmine and spider plant were 7,1 and 26,7°C, 7,6 and 26,7°Cfor spider plant.